For the first time in Canada: Quebec government legislates regarding the legal status of animals - Martine Lachance (Universitat Autonoma de Barcelona. Facultat de Dret, 2015)
In the present document, the Author comments, the Bill 54, tabled in the National Assembly in Québec, by the Minister of Agriculture, Fisheries and Food, Pierre Paradis. The purpose of this Bill is to modify Québec’s Civil Code so that animals are no longer considered to be movable property. The Author, comments the process and some declarations of the Bill, as well as other significant breakthroughs that Bill 54 will introduce.